Active control for multi-degree-of-freedom wave energy converters with load limiting. (October 2020) - Hillis, A.J.; Whitlam, C.; Brask, A.; Chapman, J.; Plummer, A.R.
Abstract: An active control strategy is a key component to enable efficient, safe and economical operation of a wave energy converter (WEC). Many strategies have been developed, but most studies are limited to simplified simulation models of WECs which are not representative of real devices. Furthermore, many studies assume perfect knowledge of the wave excitation force, which is a necessary input to many control strategies. In this work, the aim is to develop an active control strategy to maximise power capture while limiting device loading to prolong its lifetime. An approximate optimal velocity tracking (AVT) controller with a Linear Quadratic Regulator velocity tracking loop is designed. The controller is applied to a validated full-scale nonlinear model of the WaveSub multi-DOF WEC in a range of realistic sea states. Only physically measurable quantities are used in the controller, meaning the strategy developed is deployable in a real system. The performance of the actively controlled system is compared to an optimally tuned passively damped system, and power gains of up to 80% are observed. This approach shows significance in providing a substantial increase in power capture for minimal additional device cost and therefore a major improvement in cost of energy would likely result. Highlights: An active control strategy is required to maximise WEC power capture. A nonlinear multi-DOF WEC is modelled in the WEC-Sim environment. An approximate optimal velocity controller is developed, using measurable inputs. Power gains of up to 80∖% are observed across a wide range of irregular sea states.